Comparative study of gait parameters of patients undergoing distal femoral resections with non-operated and healthy limbs: a meta-analysis study - Banskota, Nishant; Fang, Xiang; Yuan, Dechao; Zhang, Wenli; Duan, Hong (Frontiers in Oncology, 2023)
Introduction Gait analysis is one of the most important components of functional outcome evaluation in patients with lower-extremity tumors. Disparities between operated limbs when compared with non-operated limbs and healthy populations based on gait parameters have rarely been studied. In the present study, we attempted to analyze the gait difference and its impacts on daily life. Methods The gait parameters of distal femoral tumor-resected patients were collected from PubMed, CNKI, MEDLINE, Embase, Cochrane, and Google Scholar till September 30, 2022, by strictly following the inclusion and exclusion criteria. Differences between gait parameters in the operated and non-operated limbs or healthy limbs of distal femoral tumor patients were analyzed based on stance phase, swing phase, cadence, and velocity. The fixed-effects and random-effects models were used to conduct a meta-analysis. Results Six studies were included according to the selection criteria. There were 224 patients in total in these studies. Standard mean differences were calculated for all of our outcomes. Our results showed that there was a minimal difference in the standard mean difference of gait parameters between operated and non-operated limbs and healthy limbs. Conclusion Distal femoral tumor resections have been associated with deficient muscle function and strength and impaired gait parameters. Minimal differences in the gait parameters highlighted the advantage of distal femoral resection when replaced with a prosthesis.